ANALISIS KESIAPAN BELAJAR SISWA DALAM MENGIKUTI PROSES PEMBELAJARAN MATEMATIKA PADA MASA PASCA PANDEMI - Desy Amelina (STKIP Subang, 2023)
This study aims to describe students' learning readiness in participating in the mathematics learning process during the post-pandemic period. This type of research is a qualitative descriptive research. The subjects of this study were all students in class V at UPT SDN 51 Yosowilangon Gresik, which consisted of 27 students. Data collection techniques for student learning readiness use observation, interviews and documentation. The results showed that students did not have good learning readiness in participating in the mathematics learning process and student learning outcomes were still low. This can be seen from the results of daily mathematics tests, students who get good grades are still 45% of the total students, and for the midterm assessment (PTS) in mathematics it is known that out of 27 students, all students still get scores below the KKM. And the factors that affect the learning readiness of class V UPT SDN 51 Gresik students consist of physical, mental, and emotional conditions, conditions of needs, motives and goals as well as conditions of knowledge, but the factors that are very dominant in influencing student learning readiness in the process of learning mathematics are condition of student knowledge. It can be seen from the 27 students of class V UPT SDN 51 Gresik, there were 22 students who stated that the students did not understand the material explained by the teacher because they had not previously been prepared or had not studied at home.